Forbidden city [videorecording] the great within - Cowling, Tim.; Geffen, Anthony; Holdsworth, May.; Moyer, Greg. ([S.l.] Discovery Communications, 1986)
Explores the history and culture of China as reflected in the art and architectural treasures of the mysterious city. The forbidden place has 9,999 rooms, 240 acres of palaces and exquisite pleasure gardens, the center of all Chinese government contains within it schools, temples, theaters and "punishment chambers." Reveals the glory and splendor of the private world of the ancient Chinese rulers.
VHS.
Credits : Narrated by Rod Steiger ; Edited by Terry Bennell.
Keywords: Forbidden City (Peking, China) -- Description; Forbidden City (Peking, China) -- History